2018
DOI: 10.1161/hypertensionaha.117.10542
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Association Between Orthostatic Hypotension at 30 Seconds Post-Standing and Late-Life Depression

Abstract: There is an established cross-sectional association between orthostatic hypotension (OH) and late-life depression. The aim of this observational study was to clarify the longitudinal association between baseline symptomatic OH (sOH-30) and incident depression in a sample of >3000 older people without baseline depression (mean age: 62 years at baseline). This study was embedded within the Irish Longitudinal Study on Ageing using data from waves 1 to 3, collected between 2009 and 2014. At 2- and 4-year follow-up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 55 publications
(79 reference statements)
2
42
1
Order By: Relevance
“…These findings are supported by prior neuroimaging studies showing a similar association between late-life depression and both global and frontal cerebral perfusion 11 , 12 . Smaller studies utilising NIRS have also demonstrated similar disparities between depressed and non-depressed participants when undertaking cognitive tasks 28 , 29 .…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…These findings are supported by prior neuroimaging studies showing a similar association between late-life depression and both global and frontal cerebral perfusion 11 , 12 . Smaller studies utilising NIRS have also demonstrated similar disparities between depressed and non-depressed participants when undertaking cognitive tasks 28 , 29 .…”
Section: Discussionsupporting
confidence: 77%
“…These findings are supported by prior neuroimaging studies showing a similar association between late-life depression and both global and frontal cerebral perfusion. 11,12 Smaller studies utilising NIRS have also demonstrated similar disparities between depressed and non-depressed participants when undertaking cognitive tasks. 28,29 However, our findings are cross-sectional and the direction of the relationship between frontal lobe cerebral perfusion and depressive symptoms remains uncertain, with limited longitudinal analyses to date.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations